The Relationship Between Gadget Usage Intensity and Learning Concentration of Junior High School Students - Margarina Kapa; Yosina Makailipessy; Jolenta Jamfaaf; Dessi Pormes; Ahmad Husin (MSJ : Majority Science Journal, 2026)
This study investigated the relationship between gadget usage intensity and learning concentration among junior high school students. The increasing prevalence of smartphones and digital devices among adolescents has raised concerns about their effects on academic performance and cognitive focus. Using a correlational quantitative approach, this study reviewed and synthesized empirical evidence from 20 recent studies (2021–2026) and conducted primary survey data analysis involving 120 junior high school students. Results indicated a significant negative correlation between gadget usage intensity and learning concentration (r = -0.614, p < 0.001). Students who used gadgets more than four hours per day demonstrated markedly lower concentration scores compared to those with limited usage. Social media use, gaming, and entertainment content were identified as the primary distraction factors. Educational use of gadgets, by contrast, showed a modest positive association with learning motivation. These findings suggest the urgent need for digital literacy programs, parental supervision frameworks, and school-based gadget management policies to mitigate adverse effects on student learning concentration.